Evaluasi Audit Internal atas Prosedur Pemberian Kredit dengan Ajaran Karma Phala sebagai Pedoman Penyelesaian Kredit Bermasalah - Kadek Irma Riskiyanti; Edy Sujana (Universitas Pendidikan Ganesha, 2021)
The aim of this study was to determine the application of credit procedures in Koperasi Pegawai Negeri (KPN) Susila Bhakti according to the established standard operating procedures, the effectiveness of internal audits especially the compliance of internal control over credit lending procedures based on the COSO component that has been implemented in KPN Susila Bhakti, and the role of the law of karma phala in solving credit problems in KPN Susila Bhakti. The method used in this research was descriptive qualitative with an empirical study approach. Data were collected through the process of interviews, documentation, and observations. The results of this study revealed that 1) compliance with credit lending procedures has not been fully implemented and resulted in non-performing loans at KPN Susila Bhakti, 2) internal audit especially internal control based on COSO that is implemented in KPN Susila Bhakti has not been fully effective as it can be seen from the results of the interview that most of the components have not been maximally carried out by KPN Susila Bhakti internally, there are still weaknesses in each component, 3) The role of the law of karma phala in resolving non-performing loans in KPN Susila Bhakti gives trust to the management and members of the cooperative to fulfill their respective obligations.